Boundary Crossings Resulting in Active Learning in Preservice Teacher Education: A CHAT Analysis Revealing the Tensions and Springboards Between Partners - Laferrière, Thérèse (Frontiers in ICT, 2018)
We present a meta-analysis of a twenty-year long university-school partnership in which pre-service teachers collaborated with cooperative teachers and peers during practicums in innovative programs that featured active learning. The partnership evolved as a design experiment. Papers presented at conferences but never submitted to a research journal were revisited applying cultural-historical activity theory (CHAT) to understand the dynamics at play, and especially boundary crossing, within the university-school partnership's activity in terms of motive/object, instruments, community, roles, and rules/policies. We point to tensions that manifested contradictions of different levels between activity systems as the innovation unfolded. Suggestions for boundary crossing when field experiences are part of an undergraduate program are made.